Technopreneur education and incubation: Designing IT technopreneurship graduate program - Abdullah, Sahadah; Md Dahalin, Zulkhairi; Rahim, Mohd Syahrir (2004)
This paper describes the design of a post-graduate program in Information Technology (IT) Technopreneurship that blends practice with theory with the primary objective of producing successful graduate IT technopreneurs. The program is designed based on close partnership between the university, the industry, and the government to ensure young and intelligent IT enthusiasts to obtain the necessary entrepreneurship knowledge and skills as well as to provide initial seed capital and adequate funding for start-offs. With the close industry linkage, business opportunities will be made available for the young technopreneuer to gain experience and exposure in the real-life environment as well as fulfilling part of the industry’s social obligation and support. The duration of the program is four semesters or two years leading to the Masters of Science in IT Technopreneurship. The program consists of four components i.e.; Self Development and Competencies through specialized technopreneurship development training, University-Industrial Linkage and intensive incubation phase to develop and commercialize IT products, Knowledge and Skill on IT and Business through Teaching Factory and Mentoring and/or solutions using the concept of Continuous Supportive System. Candidates will be selected among those who graduated with at least a 3.0 cumulative grade point average. They will have to go through a screening process in the form of an interview and aptitude test in order to get the right participants with the right attitude, having entrepreneurship characteristics, and those who possess high motivation, perseverance and interest. Major part of the curriculum are Core IT, Core Entrepreneurship, Experiential Learning and Development. One of the criteria for graduation is students will have to secure a total sales of not less than RM100,000.